Pengaruh Electronic Word Of Mouth Dan Harga Terhadap Keputusan Pembelian Dengan Brand Trust Sebagai Variabel Intervening Pada Produk MS Glow - Muhammad, Hammar Faris; Yulasmi; Aldi, Febri (Journal of Science Education and Management Business, 2025)
This research aims to find out how much the Influence of Electrinic Word Of Mouth and Price on Purchase Decisions with Brand Trust as an Intervening Variable in Ms Glow Products. The sample withdrawal method used was non-probality sampling, namely Ms. Glow consumers at Upi Yptk Padang students who happened to meet as many as 100 respondents. The method used is Stucture Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. The results of hypothesis testing show that (1) Electronic word of mouth has a non-positive and insignificant effect on Brand Trust (2) Pricing decisions do not have a significant effect on Brand Trust (3) Word Of Mouth decisions have a positive and significant effect on Purchase Decisions (4) Price Decision has a positive and significant effect on Purchase Decision (5) Brand Trust decisions have a positive and significant effect on Purchase Decisions (6) Word Of Mouth Decision Intervening the relationship between Purchase Decision and Brand Trust has a positive and significant effect (7) Intervening Price Decisions The relationship between Purchase Decisions and Brand Trust has a positive and significant effect